Surgical management of renal calculi in cases of crossed renal ectopia: A rare case series - Ponnusamy, Periasamy; K, Senthil Kumar; D, Tamilselvan; Shreyas MD (Asian Journal of Medical Sciences, 2024)
Crossed renal ectopia is a rare congenital malformation. Only 36 cases of crossed renal ectopia with calculus have been recorded in literature, even a few cases of urolithiasis in them have been surgically managed. The majority of cases in literature have been published as single case reports. We conducted a retrospective study of all the crossed renal ectopia cases admitted and managed in our department in the past 2 years. Among them, only one was without fusion. Youngest patient was 32-year-old male with crossed left kidney with calculus in the left kidney. Both the patients underwent retrograde intrarenal surgery (RIRS). Oldest patient was 80-year-old female with a right crossed kidney with pelvic calculus, who underwent open pyelolithotomy. Post-operative period was uneventful in all cases with complete stone clearance. Patients undergoing RIRS had less post-operative pain and were discharged early compared to open pyelolithotomy. RIRS is a safe and effective modality of treatment and can be considered as the first choice for the management of calculus in crossed renal ectopia in properly selected cases. However, in cases of huge stone burden and difficult anatomy, laparoscopic/open pyelolithotomy is still an attractive option for clearing the stone in a single setting, even though it has comparatively more morbidity and longer hospital stay.